Development of Regional Potential in Optimizing Economic Growth - Nuryana Haprin Dj Achmad; Patta Tope; Yunus Sading (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to identify economic potential in a particular region by determining the leading sectors and commodities that have high competitiveness. The analysis was conducted using quantitative methods through the Location Quotient (LQ) and Revealed Comparative Advantage (RCA) approaches that focus on measuring the relative advantages of economic sectors. Based on the results of the LQ analysis, the leading sector identified is the tobacco processing industry with an LQ value of 7.52, indicating a high concentration of activity compared to other regions. The next sector is the gas procurement and ice industry with an LQ value of 6.30, and the food crop subsector in the agricultural sector with an LQ value of 3.76. The RCA analysis revealed that rice is a leading commodity with the highest RCA value, namely 1.64, followed by sweet potatoes with an RCA value of 1.18. Furthermore, the RCACost analysis that takes into account the cost factor of economic activities strengthens the position of rice as a leading and sustainable commodity, with an RCACost value of 1.51.